PERBAIKAN LINE EFISIENSI PRODUKSI COFFEE MAKER PADA PT WIK - Brian Togu; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2022)
PT WIK FAR TIMUR BATAM is a German industry engaged in household appliances that produces Coffee Makers. In the manufacturing process, the Assy Head Minime line has a fairly low efficiency with a total Line Efficiency of 83.32%, the lowest station efficiency of 46.51% and an idle time of 44.8 seconds. This is because some stations are not comprehensive. The purpose of this research is to equalize station efficiency for each worker by dividing the average standard time of each worker by balancing the line with the Ranked Positional Weight method, determining the ideal number of operators for the Assy Head Minime Line and increasing production. line efficiency on the Assy Head Minime RPW (Ranked Positional) line. weight). the results of the Line Performance study from the previous 9 work stations after being repaired to 8 work stations by combining valve switch and needle plate stations with a station efficiency of 93.8% and an increase in the efficiency of the Assy Head Minime line from 83.32% to 93.41%, and the difference in efficiency between work stations is getting closer, it can be seen that the lowest efficiency is 46, 51% to 81, 27%. Regarding this, it is better than the previous efficiency, and the results of the calculation of the balance delay value also show shrinkage, because the previous inefficiency of 16.68% can be reduced or become more efficient so that the inefficiency level becomes 6.25%, and the existing idle time faces shrinkage. from 44.8 seconds changed to 14.92 seconds, and the fluency index value is 23.7 the current state is much better with a fluency index of 7.8